(untitled) (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
The swift expansion of digital financial services has reshaped how Generation Z manages personal finances. Although financial technology adoption continues to increase, differences in financial literacy may limit its effectiveness in promoting responsible financial behavior. This research analyzes both the individual and combined effects of financial technology usage and financial literacy on the financial behavior of Generation Z in Semarang City, Indonesia. A quantitative survey was conducted involving 397 respondents selected through purposive sampling. Data were analyzed using multiple linear regression to assess the relationships among variables. The results show that both financial technology usage and financial literacy have positive and statistically significant effects on financial behavior, both individually and jointly. Financial literacy exerts a relatively stronger influence, indicating that access to digital financial services alone is insufficient to ensure prudent financial management. The model explains a substantial proportion of the variance in financial behavior. These findings emphasize the importance of integrating financial knowledge with digital financial access to foster responsible and sustainable financial practices among young adults